2015
DOI: 10.1039/c5dt01203a
|View full text |Cite
|
Sign up to set email alerts
|

A chromium precursor for the Phillips ethylene trimerization catalyst: (2-ethylhexanoate)2CrOH

Abstract: The conventional Phillips ethylene trimerization catalyst prepared by reacting Cr(EH)3 (EH = 2-ethylhexanoate), 2,5-dimethylpyrrole (Me2C4H2NH), Et3Al, and Et2AlCl in an aromatic hydrocarbon solvent was improved to obtain a congener composed of a new chromium precursor (EH)2CrOH, (Me2C4H2N)AlEt2, and Et3Al·ClAlEt2. Reaction of CrCl3 with 3 equiv. Na(EH) in water did not generate Cr(EH)3, but unexpectedly produced (EH)2CrOH. In comparison with the erratic catalytic performance of the original Phillips system, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 44 publications
1
27
0
Order By: Relevance
“…[8] The activity attained is also more than 4 times higher than the commercially used Chevron Phillips trimerization catalyst (1 000 Kg/g-Cr/h). [13] 4 ] À further supported that the bulky R 3 Si-substituents are crucial not only to achieve extremely high activity but also to minimize the generation of the problematic side product PE. X-ray crystallographic studies revealed that the prepared [(PNP)-CrCl 2 ] + [B (C 6 F 5 ) 4 ] À species existed as a dinuclear Cr III complex sharing the chloride ligand and coordinated by an additional CH 3 CN donor.…”
Section: Full Papersmentioning
confidence: 94%
See 2 more Smart Citations
“…[8] The activity attained is also more than 4 times higher than the commercially used Chevron Phillips trimerization catalyst (1 000 Kg/g-Cr/h). [13] 4 ] À further supported that the bulky R 3 Si-substituents are crucial not only to achieve extremely high activity but also to minimize the generation of the problematic side product PE. X-ray crystallographic studies revealed that the prepared [(PNP)-CrCl 2 ] + [B (C 6 F 5 ) 4 ] À species existed as a dinuclear Cr III complex sharing the chloride ligand and coordinated by an additional CH 3 CN donor.…”
Section: Full Papersmentioning
confidence: 94%
“…Ethylene was purified by contact with molecular sieves and copper for more than 12 h under 48 bar pressure. 1 H NMR (600 MHz), 13 C NMR (150 MHz), and 31 P NMR (243 MHz) spectra were recorded using a JEOL ECZ 600 spectrometer. Continuous wave X-band EPR spectra were collected at 5 K on a Bruker EMX plus 6/1 spectrometer with the experimental parameters of 1 mW microwave power, 10 G modulation amplitude, and 5 scans at KBSI Western Seoul Center Korea.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Typically, ethylene oligomerization is conducted in a solvent media at both industrial and laboratory scales, using the Chevron-Phillips catalytic system. Typical oligomerization solvents employed in both academic laboratories and industrial settings are either toluene or some saturated alkanes, such as methylcyclohexane [24][25][26]. For this reason, the effect on the catalytic cycle of the two most widely used solvents, methylcyclohexane and toluene, was studied.…”
Section: Effect Of Solventmentioning
confidence: 99%
“…saturated alkanes such as methylcyclohexane [24,25,26]. For this reason, the effect of two 280 most widely used solvents, methylcyclohexane and toluene, on the catalytic cycle was 281 studied.…”
mentioning
confidence: 99%